Retention of arthroscopic shoulder skills learned with use of a simulator. Demonstration of a learning curve and loss of performance level after a time delay. - Howells, N; Auplish, S; Hand, G; Gill, R; Carr, A; Rees, J (2009)
In orthopaedic surgery, arthroscopy is an irreplaceable diagnostic and interventional tool, and its breadth of use is increasing. The aim of this study was to investigate the surgeon's capacity for retention of an unfamiliar arthroscopic skill.Six fellowship-trained lower-limb surgeons were given standardized instruction regarding the performance of an arthroscopic Bankart suture on a laboratory-based simulator. They performed three single Bankart sutures on each of four occasions, one to two weeks apart. Six months later, the same surgeons repeated the study. They received no further instruction or guidance. Their performance was objectively assessed with use of validated motion-analysis equipment to record the total path length of the surgeon's hands, number of hand movements, and time taken to perform the sutures.A learning curve showing significant and objective improvement in performance was demonstrated for all outcome parameters in both experiments (p < 0.005). The learning curve at six months was a repeated learning curve showing no significant difference from the initial learning curve.This study objectively demonstrated a loss of all of the initial improvement in the performance of an arthroscopic Bankart suture following a six-month interval in which the surgeons did not do the procedure.